2021
DOI: 10.1016/j.cmet.2021.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-associated hyperleptinemia alters the gliovascular interface of the hypothalamus to promote hypertension

Abstract: Summary Pathologies of the micro- and macrovascular systems are a hallmark of the metabolic syndrome, which can lead to chronically elevated blood pressure. However, the underlying pathomechanisms involved still need to be clarified. Here, we report that an obesity-associated increase in serum leptin triggers the select expansion of the micro-angioarchitecture in pre-autonomic brain centers that regulate hemodynamic homeostasis. By using a series of cell- and region-specific loss- and gain-of-functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 71 publications
(82 reference statements)
4
59
0
1
Order By: Relevance
“…On the other side, although histochemical staining confirmed the localization of collagen around the fenestrated capillaries of the ME, it did not show an evident higher level of staining in HFD compared to CTRL, which was possibly due to the low sensitivity of the technique. However, hypothalamic hypervascularization and micro-angioarchitecture anomalies consisting of increased extracellular matrix protein deposition, collagen IV, basal membrane size and vascular impairments were recently documented [ 51 ] and are consistent with other report [ 31 ]. Interestingly, diet-induced hyperleptinemia was recently demonstrated to lead to alteration in the HIF1-α/VEGF signaling in hypothalamic astrocytes, which is in turn responsible for the obesity-induced hypertension [ 51 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the other side, although histochemical staining confirmed the localization of collagen around the fenestrated capillaries of the ME, it did not show an evident higher level of staining in HFD compared to CTRL, which was possibly due to the low sensitivity of the technique. However, hypothalamic hypervascularization and micro-angioarchitecture anomalies consisting of increased extracellular matrix protein deposition, collagen IV, basal membrane size and vascular impairments were recently documented [ 51 ] and are consistent with other report [ 31 ]. Interestingly, diet-induced hyperleptinemia was recently demonstrated to lead to alteration in the HIF1-α/VEGF signaling in hypothalamic astrocytes, which is in turn responsible for the obesity-induced hypertension [ 51 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, hypothalamic hypervascularization and micro-angioarchitecture anomalies consisting of increased extracellular matrix protein deposition, collagen IV, basal membrane size and vascular impairments were recently documented [ 51 ] and are consistent with other report [ 31 ]. Interestingly, diet-induced hyperleptinemia was recently demonstrated to lead to alteration in the HIF1-α/VEGF signaling in hypothalamic astrocytes, which is in turn responsible for the obesity-induced hypertension [ 51 ]. Thus, it is possible that the detected Arc-ME increase in collagen is a consequence of the obesity-induced hypothalamic microangiopathy, which is a phenomenon with critical pathophysiologic implications.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, the sites of hypertensive effects of leptin have not been determined. Earlier studies have suggested that the central regulation of blood pressure by leptin is localized to the dorsomedial hypothalamus (Simonds et al, 2014;Gruber et al, 2021). Here, we showed that the systemic blockade of leptin receptors in NZO mice reduced blood pressure, but did not affect ventilation and metabolism, since food intake remained unchanged.…”
Section: Potential Sites and Mechanisms Of Leptin Actionsupporting
confidence: 50%
“…Moreover, leptin is involved in blood pressure regulation [36], and obese patients usually have hypertension. Decreased leptin concentration could be engaged in the SBP reduction observed in this study (Table 4).…”
Section: Discussionmentioning
confidence: 99%